Материалы к фауне пухоедов воробьиных птиц Украины. Сообщение IV. Philopterinae (Mallophaga, Ischnocera). Ч. 2. - Федоренко, И.А. (Вестник зоологии, 1978)
44 species of Mallophaga from the Philopterus genus are found on Passeriformes of the Ukrainian fauna. The occurrence indexes of some Philopterus species vary gonsiderably: from 11.1% for Ph. fringillae on Passer montanus to 80.0% for Ph. merulae on Turdus merula. The average intensity of infestation was not above 23 samples (the maximum intensity on one individuum being 108 samples). Seven species of the Philopterus genus are registered first for the USSR fauna. Five species of Passeriformes are observed as new hosts for representatives of the Philopterus genus (Phylloscopus collybitus Vicillot, P. sibilator (Bechstein), Sylvia nisoria (Bechstein), S. borin (Boddaert), Oenanthe hispanica pleschanka). Two new for science species are described: Ph. sittae sp. n. from Sitta europaea L. and Ph. nativus sp. n. (see Part I) from Turdus torquatus alpestris Brehm.